Economic Revitalization of Suka Maju Village through a Productive Waqf Model: Strategies and Implementation - Al-Munawar, Rizky; Wargo; Fatimah, Siti; Daud; sarmiati (Journal of Economics and Social Sciences (JESS), 2025)
Economic empowerment of rural communities is a critical aspect of sustainable national development. Suka Maju Village possesses substantial local resource potential but faces various challenges in optimizing these resources, such as limited business capital, low financial literacy, and inadequate infrastructure. This study examines the economic empowerment strategies of the Suka Maju community through the implementation of productive waqf as an innovative and sustainable Islamic economic instrument. A qualitative case study approach was employed to explore the management practices of productive waqf and its impact on improving community welfare. The findings indicate that a participatory and transparent productive waqf management model can increase community income by 30–50%, while simultaneously strengthening social capital through mutual cooperation and community solidarity. The active role of community leaders in adaptive education and communication proved to be a key factor in the program’s success. This study concludes that professional and participatory governance of productive waqf not only supports the sustainability of economic empowerment programs but also provides a replicable framework for the development of other villages grounded in strong socio-religious values